Meningkatkan Kemampuan Literasi Awal Pada Anak Usia Dini 4-5 Tahun Dengan Metode Pembelajaran Berbasis Permainan Story Cube - Nur Tanfidiyah; Dhea Az Zahra (Journal Ashil: Jurnal Pendidikan Anak Usia Dini, 2026)
The problem in this study is that some early childhood children are less interested in early literacy interests related to language skills which can be seen in the lack of confidence of children when conveying something in front of others. This is caused by the fact that the learning media used to teach literacy is less interesting and still often uses magazines. This study aims to improve early literacy in the aspect of language skills of children aged 4-5 years through the Story Cube game method. This study aims to use the Classroom Action Research (CAR) type with the subjects of class A students at BA Aisyiyah Sonorejo 1 Sukoharjo, totaling 21 children consisting of 9 girls and 12 boys. The results show that Group A children improve their early literacy skills when they use this story cube-based game technique each cycle. Furthermore, the number of children in the BSH and BSB categories increased to 66.7% after the action in cycle I and to 80.9% after the action in  cycle II. Therefore, this study is considered successful because it has covered the predetermined success value.